INDONESIAN PREPOSITIONAL PHRASES IN THE SHORT STORY HYANG IBU BY MADE ADNYANA OLE - Ni Luh Gede Liswahyuningsih; I Wayan Dede Putra Wiguna; Kadek Windari; I Wayan Agus Sukmadana; Ni Komang Sabina Sanji Putri (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2023)
This study aims to determine the syntactical and functional structure of Indonesian prepositional phrases in the short story "Hyang Ibu" by Made Adnyana Ole. The focus of the study is prepositional phrase markers and their functions in the phrase. This research is a descriptive qualitative research. The data were identified by underlining all simple sentences that have prepositional phrases in it and writing them on several sheets of paper and classified by its structure. The data were analyzed by taking samples of each type of prepositional phrase function within a sentence. The data were then described in more detail on the internal structure of prepositional phrases supported by the X-bar chart. The results of this study showed that the minimal structure of a PP is a preposition and complement. The internal structure of Indonesian PP found in the data source is formed by a core in the form of preposition and followed by complements and specifiers. Based on the categorical pattern of fillers of prepositional phrases, prepositions di-, ke- and dari- become the core of the phrase. The use of the prepositional phrase di- in the short story "Hyang Ibu" serves to state the setting or place of its existence and medium. The phrase preposition ke- serves to express the direction (setting of place) or purpose. Then the prepositional phrase dari- function is to state the background or place of origin also the comparison meaning.